2020
DOI: 10.1021/acsomega.0c04588
|View full text |Cite
|
Sign up to set email alerts
|

Lyophilized Amorphous Dispersion of Telmisartan in a Combined Carrier–Alkalizer System: Formulation Development and In Vivo Study

Abstract: Telmisartan suffers from low oral bioavailability due to its poor water solubility. The research work presents a formulation of solid dispersed (SD) telmisartan formulation as a ternary mixture of a drug, a polymeric carrier (poly(vinylpyrrolidone) (PVP) K30), and an alkalizer (Na 2 CO 3 ). The preparation method, which was lyophilization of an aqueous solution containing the ingredients, was free from any organic solvent. The developed SD formulations resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…In solid dispersion, characteristic arteether peaks are either absent or present with significantly low intensity compared to that of the pure drug or its physical mixture. Reduction in peak intensities indicates loss of crystallinity . When a drug is dissolved in a solvent in the presence of a polymeric matrix, followed by solvent evaporation, it becomes dispersed in the polymeric matrix in either an amorphous or molecular dispersion form.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In solid dispersion, characteristic arteether peaks are either absent or present with significantly low intensity compared to that of the pure drug or its physical mixture. Reduction in peak intensities indicates loss of crystallinity . When a drug is dissolved in a solvent in the presence of a polymeric matrix, followed by solvent evaporation, it becomes dispersed in the polymeric matrix in either an amorphous or molecular dispersion form.…”
Section: Resultsmentioning
confidence: 99%
“…However, they have their drawbacks, such as the complexity of the SLN formulation or the high surfactant content of SEDDS. Solid dispersion is another popular approach to enhancing the dissolution of the poorly water-soluble drug. , For BCS class II drugs with dissolution rate-dependent oral absorption, the solid dispersion approach can significantly improve their oral bioavailability. , There are more than 30 US FDA-approved drug products based on the solid dispersion approach, and the number is increasing yearly . In amorphous solid dispersion (ASD), the active ingredient is dispersed in a substantially amorphous form within an excipient matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following equation was used to compute the drug entrapment efficiency: (4) For drug content, about 1 mL of transfersome, ethosome, and transethosome formulations equivalent to 1000 µg of BEN was properly diluted with methanol to reach a final concentration of 100 µg/ml. The HPLC technique was used to evaluate the drug content in samples using the following equation [21]:…”
Section: Determination Of Drug Entrapment Efficiency (Ee%) and Drug C...mentioning
confidence: 99%
“…The developed SD formulations resulted in a significant improvement in in vitro dissolution compared to pure drug. 62 K Wlodarski, developed tadalafil (Td) six different solid dispersions in the following polymers: HPMC, MC, PVP, PVP-VA, Kollicoat IR and Soluplus by freeze-drying. Apparent solubility and intrinsic dissolution rate studies revealed the greatest, a 16-fold, increase in drug solubility and a significant, 20-fold, dissolution rate enhancement for the Td/PVP-VA solid dispersion in comparison with crystalline Td.…”
Section: Lyophilisationmentioning
confidence: 99%